ENERGY DRINKS CONSUMPTION PATTERN, PERCEIVED BENEFITS AND ASSOCIATED ADVERSE EFFECTS AMONGST STUDENTS OF UNIVERSITY OF DAMMAM, SAUDI ARABIA - Alsunni, Ahmed A; Badar, Ahmed (Journal of Ayub Medical College Abbottabad, 2011)
Background: There are safety concerns about energy drinks alongside marketing claims of physiological and behavioural benefits. There is no scientific data about usage of energy drinks in Saudi Arabia. This study determined consumption patterns of energy drinks as well as perceived benefits and side effects amongst students at a Saudi university. Methods: This study was carried out in students of University of Dammam from October to December 2010. A questionnaire about energy drink use, reasons for use, benefits and side effects experienced was distributed amongst the university students. Frequencies of responses and differences between male and female students were analysed. Results: A total of 412 students (282 males and 130 females) responded, out of whom 54.60% males and 26.15% female students were energy drink users. Mean age at first use was significantly (p<0.05) less in female students. Inspirations for first time use were friends (both genders) and curiosity (males mainly). Most students did not have a fixed frequency of use. The commonest reasons for use were company of friends, to keep awake, for more energy and for better performance in driving, sports or exams. Amongst many the commonest (p<0.05) benefit reported was ability to stay awake longer. The students reported a number of adverse effects. Increased urination and insomnia were the commonest in males and females respectively. Only 36.70% males and 14.28% females never experienced an adverse effect. Conclusion: A significant proportion of students at university of Dammam use energy drinks, they have reported a number of effects (perceived as benefits) along with a variety of adverse effects. Keywords: Energy Drinks, Students, Saudi Arabia, Benefits, Adverse effects